How mindfulness and coping styles shape anxiety and depression in metastatic gastrointestinal cancer - Bakkal Temi, Yasemin; Gareayaghi, Aila; Baydar, Ece; Çıtakkul, İlkay; Çabuk, Devrim; Kefeli, Umut; Uygun, Kazım (Frontiers in Psychology, 2025)
ObjectivesSignificant psychological distress is prevalent among patients with advanced gastrointestinal cancer, underscoring the need to investigate the roles of mindfulness and coping strategies in shaping emotional outcomes. However, this relationship has not yet been sufficiently explored. Therefore, this study aimed to investigate the associations between mindfulness, coping styles, and emotional distress (anxiety and depression) in individuals with advanced gastrointestinal cancer.MethodsThis cross-sectional study enrolled 110 patients with stage IV gastrointestinal cancer who received palliative chemotherapy. Participants completed Turkish versions of the Mindful Attention Awareness Scale, Mental Adjustment to Cancer scale, and Hospital Anxiety and Depression Scale. Sociodemographic and clinical data were collected using a patient information form. Data were analyzed using non-parametric tests and correlation analyses to examine group differences and associations among study variables.ResultsOur findings indicated significant associations between trait mindfulness, coping strategies, and emotional symptoms. Specifically, trait mindfulness was positively correlated with adaptive coping (r = 0.245, p = 0.010) and anxiety (r = 0.455, p < 0.001), whereas it was negatively correlated with maladaptive coping (r = −0.326, p = 0.001). Moreover, participants who employed maladaptive coping strategies reported lower levels of mindfulness. No significant differences in depression were observed between coping style groups. Notably, the positive correlation between adaptive coping strategies and anxiety symptoms highlights the complex nature of the coping mechanisms.ConclusionThese findings underscore the importance of contextualizing coping constructs, and suggest that mindfulness, despite its paradoxical relationship with anxiety, may mitigate reliance on maladaptive strategies. Routine psychological screening and personalized psychosocial support should be incorporated into oncological care to facilitate emotional adjustment.